SPECTRALLY COMPARISON BEETWEEN TM 5 & ETM +7 BANDS - Al Ramahie, Fouad (Iraqi Journal of Science, 2024)
Landsat-7 Enhanced Thematic Mapper Plus (ETM+) sensor offers severalenhancements over the Landsat-5 Thematic Mapper (TM) sensors, including increasedspectral information content, improved geodetic accuracy, reduced noise, reliablecalibration, and matching scenes were recorded by both, and improved spatial resolutionof the thermal band. In this paper, we present some comparisons between Landsat-7ETM+ and Landsat-5 TM imagery in order to quantify these improvements. Practically,we find that the ETM+ continues the record of TM observations, and, in many respects,substantially improves upon the earlier sensor. Specific improvements include lowerspatial noise levels, improved information content, and geodetic accuracy ofsystematically corrected products to 50–100 m. These improvements are likely benefitsfor land-cover mapping and change detection applicat